Arahan Penataan Ruang Jalan Sebagai Ruang Publik Pada Kawasan Komersial Kajian Pada Setting Elemen Fisik Dan Aktifitas Studi Kasus : Jalan Pemuda â Kota Magelang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The area of Jalan Pemuda in Magelang County, which is from the beginning had already under the Dutch authority and Chinese merchants concentration, was known as an important regional passing way. Because of its strategic location and enclosed by two important generators-Alun-alun and Pasar Rejowinangun- at both of its ends, now Jalan Pemuda has developed into a main commercial center including various informal business or street vendors (mention : PKL). To evaluate the condition of Jalan Pemuda as a public space in commercial area towards a representative condition, the study included physical setting aspect of the street wall and other physical elements, as well as the aspect of activities setting, for both the "wall" and the street space in the discussion. Street wall could be formed by the character of buildings, street vendors, and tree lines along the street, while street space dominated by the activity that being observed, is the activity of pedestrian, street vendors, and parking, along with physiology and psychology needs of the user. The strategic issues of this context were : 1) the formal character of the street wall is unattractive